The role of governance, ICT and bad loans in Australian bank efficiency: an empirical study - Salim, Ruhul; Hoque, M.; Suyanto, Suyanto (School of Economics and Finance, Curtin University of Technology, 2010)
This paper analyzes the impact of governance, information and communications technology (ICT) and bad loans on bank efficiency over the period 1997-2007. Using linear programming-based data envelopment analysis, the study shows that the overall efficiency of Australian banks is influenced by a consistent growth of technicalefficiency since 1997, with major banks showing relatively higher levels of technical efficiency than regional banks. The results from the Malmquist productivity index reveal that technological progress contributes substantially to banks' productivity growth. Furthermore, the results from the common effect panel data model show that bad loans and poor governance have negative effects while ICT has apositive impact on banks' technical efficiency.